2021
DOI: 10.3389/fpsyg.2021.751176
|View full text |Cite
|
Sign up to set email alerts
|

Modern Physical Education and Its Influence on Students’ Entrepreneurial Psychology in Sports Universities

Abstract: This study aims to explore the entrepreneurial psychology of physical Education (PE) students under the “Internet+”environment, to cultivate and improve the entrepreneurial consciousness of PE students, taking the realization of students’ sense of self-efficacy as an intermediary factor. The new educational technology in modern PE is analyzed first. Specifically, the motion sensing technology based on human-computer natural interaction can be used for training, so that learners can effectively improve their ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…The main findings, according to the European Commission (EDEI, 2012, p.7) regarding higher education institutions in Europe, indicate that "entrepreneurship education has a positive impact on the entrepreneurial mindset of young people, their intentions towards entrepreneurship, employability and finally, their role in society and the economy." These and other related findings revealed that the value of education in developing the entrepreneurial potential of future graduates increasingly attracts the attention of researchers and the academia (González-Serrano et al, 2021;Gonzalez-Serrano et al, 2021;Zhou et al, 2021).…”
Section: Introductionmentioning
confidence: 79%
“…The main findings, according to the European Commission (EDEI, 2012, p.7) regarding higher education institutions in Europe, indicate that "entrepreneurship education has a positive impact on the entrepreneurial mindset of young people, their intentions towards entrepreneurship, employability and finally, their role in society and the economy." These and other related findings revealed that the value of education in developing the entrepreneurial potential of future graduates increasingly attracts the attention of researchers and the academia (González-Serrano et al, 2021;Gonzalez-Serrano et al, 2021;Zhou et al, 2021).…”
Section: Introductionmentioning
confidence: 79%
“…needs support. (Chevalier et al, 2022;Grivokostopoulou et al, 2019;Zhou et al, 2021) explained that business knowledge and skills can be acquired through extracurricular activities and can encourage boys and girls to study theory Business. Finally, entrepreneurial mentality is associated with negative emotions that predict self-management strategies, particularly in the face of business challenges.…”
Section: Entrepreneurial Mindsetmentioning
confidence: 99%